A nonlocal coupled damage-plasticity model for the analysis of ductile failure - Nguyen, G; Korsunsky, A; Belnoue, J (Elsevier, 2015)
This paper presents a nonlocal coupled damage-plasticity model for the analysis of ductile fracture. The proposed model makes use of both damage mechanics and plasticity theories and hence is able to capture the pre-peak hardening and post-peak softening responses as well as the stiffness reduction of the material during the deformation and fracture processes. Nonlocal regularisation technique is used as an enhancement to the proposed damage-plasticity model to deal with softening related problems in the constitutive modelling and the failure analysis. Emphasis is put on the determination of model parameters with a novel calibration procedure, based on the experimental technique (Korsunsky and Kim, 2005) on the measurement of essential and non-essential works of fracture, proposed and effectively used for the model calibration. It is shown that all model parameters can be properly calibrated based on the proposed method, and experimental results, making the model attractive for practical applications. The proposed nonlocal model enables the stress update to be carried out pointwise, and hence facilitates the implementation of the model in existing finite element codes. Numerical examples are used to demonstrate the capability of the proposed model.